Clinical and Radiological Long-term Results After Implant-Free, Autologous, Iliac Crest Bone Graft Procedure for the Treatment of Anterior Shoulder Instability. Issue 12 (October 2018) - Moroder, Philipp; Plachel, Fabian; Becker, Johannes; Schulz, Eva; Abdic, Shejla; Haas, Maximilian; Resch, Herbert; Auffarth, Alexander
Background: The implant-free, autologous, iliac crest bone graft procedure (J-bone graft) for the treatment of anterior shoulder instability shows low rates of recurrent dislocations and moderate progression of instability arthropathy in the midterm follow-up. Purpose: To analyze the clinical and radiological long-term results of the J-bone graft procedure. Study Design: Case series; Level of evidence, 4. Methods: A total of 46 patients (47 shoulders) with anterior shoulder instability and a relevant bony glenoid defect who received a J-bone graft between 1993 and 2000 and who were previously subjected to a midterm follow-up (mean, 8 years) were included. In total, 34 patients and 35 shoulders (74%) were clinically and radiologically assessed after a mean follow-up of 18 years (range, 15-23 years). Patients were assessed in terms of pain, bilateral active range of motion, and strength; in addition, the Western Ontario Shoulder Instability Index (WOSI), the Rowe Score, and the Subjective Shoulder Value (SSV) were obtained. Both an apprehension test and a relocation test were performed. Radiological imaging included bilateral radiographs (true anteroposterior and axillary view) to determine the grade of instability arthropathy. Results: At final follow-up, a mean WOSI score of 295 (range, 0-1765), Rowe Score of 94 (range, 55-100), SSV of 90% (range, 20%-100%), and pain level of 0.5 (range, 0-4) were noted. Slight differences were detected in active range of motion between the affected and the contralateral side: flexion 178° vs 179° ( P = .325), abduction 177° vs 179° ( P = .225), external rotation 63° vs 67° ( P = .048), high external rotation 77° vs 82° ( P = .007), internal rotation 8.8 vs 9.4 points ( P = .017), and high internal rotation 70° vs 74° ( P = .026). No significant strength deficit of the affected side was noticed. In 1 patient, a traumatic redislocation with fracture of the bone graft was observed 6 weeks after index surgery. No further recurrences were found during the follow-up period. Negative apprehension and relocation tests were confirmed in 77% of the shoulders, while 23% were positive. At final follow-up, 9 shoulders showed no signs of instability arthropathy (26%), mild arthropathy was revealed in 22 shoulders (63%), moderate arthropathy was noted in 3 shoulders (9%), and signs of severe arthropathy were found in 1 shoulder (3%) (collective instability arthropathy score, 0.9). The collective instability arthropathy score on the contralateral side was 0.4 ± 0.8 with no instability arthropathy in 24 shoulders (69%), mild arthropathy in 8 shoulders (23%), moderate signs of arthropathy in 2 shoulders (6%), and severe arthropathy in 1 shoulder (3%) at the time of follow-up examination (collective instability arthropathy score, 0.4). The overall difference between affected shoulders and contralateral shoulders was significant ( P = .005). Conclusion: The J-bone graft procedure for the treatment of recurrent anterior shoulder instability shows excellent results regarding stability and function after a mean follow-up period of 18 years. However, the development of instability arthropathy of the affected shoulder is not prevented by this procedure.